(untitled) (Indian Journal of Applied-Basic Medical Sciences, 2020)
Background ; A period of starvation (“nil by mouth”- NBM) is common practice after gastrointestinal surgery during which an intestinal anastomosis has been formed. So Early Entearl Feeding requires scrutiny in the term of indications ,success and failure to give benefit to patient. Methodology; The study is carried out on in patients admitted in municipal general hospital of Ahmedabad . A total of 34 patients of intestinal resection anastomosis and perforation primary repair were included in the study and data were collected in the prescribed performa consisting details of patient’s history , clinical findings, operative findings, post operative course and complications, and outcome. Results ; Observation and analysis of the data of present series was interesting and important aspects were compared with standard series .Wound Infection was Common Complication in both group .Morbidity and Other Complications were significantly low in early Enteral feeding Group Patients. Conclusion; Early enteral feeding is safe, effective, feasible and cost effective in post operative patients of resection and anastomosis or perforation primary repair.